Performance studies on Macro fiber composite (MFC) under thermal condition using Kirchhoff and Mindlin plate theories. (September 2017) - Pandey, Akash; Arockiarajan, A.
Highlights: A 2D Finite element model is developed based on Kirchhoff and Mindlin plate theories to study the actuation performance of MFC. Developed model is extended to predict the performance behaviour of MFC under non-linear variation of temperature across the thickness as well as linear variation of electric field in the MFC. Experimental setup has been developed and measurements are carried out under thermal conditions. The influence of plate thickness and piezoelectric fiber angle in MFC is reported at the elevated temperature. Graphical abstract: Abstract: Macro fiber composite (MFC) has seen a surge in the applications of energy harvesting, vibration control and health monitoring due it its high flexibility, improved strength and high blocking force. For studying the actuation performance of MFC under electrical and thermal loading, a 2D FE model based on Kirchhoff and Mindlin plate theory is developed and validated using experimental observations. Effect of non-linear variation of temperature across the thickness of the whole structure is studied. The present model is also extended to study the effect of linear variation of the electric field across the thickness of d 31 type MFC. Detailed stress analysis is carried out to find the high stress area on the plate. A parametric study is carried out to find the influence of plate thickness and piezoelectric fiber angle on actuation performance.